Effect of Different Improvement Methods on Yield and Botanical Composition of Natural Pasture in Salur Village of Ladik Town - Aydin I.; Uzun F. (TUBITAK, 2000)
This research was conducted to determine the most suitable improvement methods applicable in pastures of the central Black Sea Region. A natural pasture in Salur Village of Ladik Town was used. Fertilizer (10 kg/da N+8 kg/da P2O5), soil aeration, herbicide, broadcast seeding, deep cutting and some combinations of them were chosen and applied as pasture improvement methods in 1996-1998. The results indicated that deep cutting and herbicide application had different effects on hay and protein yields according to year. None of the methods affected the botanical composition of the pasture. Hay yield and botanical composition of the pasture were significantly different among the experiment years. In the second and third years of the experiment, higher hay yield and higher grass and legume percentages were produced than in the first year. According to the average data of the 3-year experiment the least hay yield (367 kg/da) was obtained from control (untreated) plots, the highest yield (530 kg/da) from fertilized, broadcast seeding and soil aerated plots.
Ladik ilcesi Salur Koyu merasinda farkli islah metodlarinin ot verimi ve botanik kompozisyon uzerine etkileri